2021
DOI: 10.13171/mjc02101211565lk
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis, antioxidant activity, and nephroprotective effect of the Raphanus sativus aqueous extract

Abstract: <p class="Default">In Morocco, Raphanus sativus is a widespread traditional medicinal plant used to treat various kidney diseases such as nephropathy.</p><p class="Mabstract"><strong>Objective</strong>:<strong> </strong>The present study aims to evaluate the protective effect of the <em>R. sativus </em>aqueous extract against the gentamicin-induced acute nephrotoxicity in rats.</p><p class="Mabstract"><strong>Methods</strong>: Rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Injecting GM also causes hepatotoxicity, which contributes to damage of the hepatocyte membranes, and then an increase in the blood GGT. These abnormalities in biochemical parameters and tissue damage produced by the GM are consistent with previously published work [ 12 , 35 , 36 , 37 ]. However, the daily administration of the ZLF aqueous extract 3 h before the injection of GM significantly restored these disorders provoked by the GM.…”
Section: Discussionsupporting
confidence: 92%
“…Injecting GM also causes hepatotoxicity, which contributes to damage of the hepatocyte membranes, and then an increase in the blood GGT. These abnormalities in biochemical parameters and tissue damage produced by the GM are consistent with previously published work [ 12 , 35 , 36 , 37 ]. However, the daily administration of the ZLF aqueous extract 3 h before the injection of GM significantly restored these disorders provoked by the GM.…”
Section: Discussionsupporting
confidence: 92%
“…The effectiveness of antioxidant activity was determined through the application of the 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging assay, which was utilized to establish the antioxidant properties of the substance in question, as reported in [ 82 ], with slight modification. The essential oil was diluted in series and 1 mL of each dilution was combined with 1 mL of 0.1 mM methanolic DPPH solution.…”
Section: Methodsmentioning
confidence: 99%
“…The study also demonstrated a significant decrease in renal biomarkers Beta 2-macroglobulin (β2M) and kidney injury molecule-1 (KIM-1) and nitric oxide, in addition to the decrease in inflammatory marker IL-6 (24). Similarly, the ethanol extract of A. lanata and aqueous extracts of A. paniculata and R. sativus demonstrated nephroprotection in Gen-induced nephrotoxicity in rats (25)(26)(27). The ethanol extract of A. lanata demonstrated a significant decrease in BUN, Sr. and Cr.…”
Section: Introductionmentioning
confidence: 81%
“…A. lanata is commonly employed in Siddha system of medicine and is stated to exhibit a marked protective effect against Geninduced nephrotoxicity in the rat (32,33). Furthermore, the nephroprotective potential of A. paniculata and R. sativus has been confirmed by several studies (26,27,34,35).…”
Section: Discussionmentioning
confidence: 96%